Risposta trascrittomica di metazoi antartici al riscaldamento ambientale - GRECO, SAMUELE (Università degli Studi di Trieste, 2022)
In this thesis RNA-sequencing tools are applied on some representatives of the antarctic trophic chain exposed to a non lethal temperature increase, as to understand and model their response to the increase in temperature expected to happen in this decade, in order to extend eventual functional conclusions to other temperate stenotherm organisms such as those living at extreme depths. RNA-sequencing consists in a set of powerful and sensible tools that allow qualitative and quantitative measurements in gene expression, pairing molecular analyses with state-of-the-art statistics and computer science. The aforementioned sensitivity, in synergy with a proper experimental design, allowed studying not only the response to a temperature increase, but also to the experimental condition itself (i.e. stabling of wild animals in tanks). The notothenioid fish Trematomus bernacchii (from which muscle, gills and brain were sampled), the scallop Adamussium colbecki (from which gills, mantle and digestive gland were sampled), the amphipod Pseudorchomene plebs and the tardigrade Acutuncus antarcticus are the models of choice of this work. In particular T. bernacchii was the most responsive of the bunch, specially in the brain tissues, where the temperature (+1.5°C increase) induced upregulation of genes involved in immune response and inflammatory state after 7 days of exposure. After 20 days of heat exposure many pathways related to synapse function and structure were altered, suggesting an on-going profound alterations in the tissue, which may also be the result of the combined effect of heat and the impossibility to avoid it in captivity. Even more profound effects were observed in the response to time in experimental tanks, as an important shift in gene expression was observed in the brain, suggesting profound changes in the neural pathways, including those involved in specific stress perception. The scallop A. colbecki did not show significant change in gene expression patterns in response to heat, but a small change was ...